Pendekatan Sosial Terhadap Sistem Qanun dalam Perwujudan Hak Asasi Manusia - Zainal Fadri (IAIN Batusangkar, 2022)
This study aims to provide an approach to the qanun system in force in Aceh, then carry out a social approach to produce a study as a recommendation for government policies in dealing with the problems that occur. The method used is descriptive qualitative with a literature approach. The research was carried out by comparing theories and concepts and looking at conditions in the field in the implementation of qanun law, then analyzing the concept of humanity. The results of this study illustrate that qanun law is part of Islamic law which is implemented in Aceh and is used as a source of law. The implementation of the qanun law is a form of special approach in humanitarian matters that has been made various improvements so that it can be recognized as a form of law in Indonesia as a form of repertoire and wealth of local wisdom, although it can only be applied in Aceh.